Detection of EGFR Mutations in cfDNA and CTCs, and Comparison to Tumor Tissue in Non-Small-Cell-Lung-Cancer (NSCLC) Patients - Liu, Haiyan E.; Vuppalapaty, Meghah; Wilkerson, Charles; Renier, Corinne; Chiu, Michael; Lemaire, Clementine; Che, James; Matsumoto, Melissa; Carroll, James; Crouse, Steve; Hanft, Violet R.; Jeffrey, Stefanie S.; et al. (Frontiers in Oncology, 2020)
Lung cancer is the leading cause of cancer-related mortality worldwide. Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) therapies, based on the evaluation of EGFR mutation, have shown dramatic clinical benefits. EGFR mutation assays are mainly performed on tumor biopsies, which carry risks, are not always successful and limited in time. In order to detect secondary EGFR mutations, which cause resistance to 1st and 2nd generation TKI’s and lead to the administration of a 3rd generation drug, effective and non-invasive monitoring of the EGFR mutation status is needed. Liquid biopsy analytes, such as circulating tumor cells (CTCs) and circulating tumor DNA (cfDNA), allow such monitoring over the course of the therapy. The aim of this study was to develop and optimize a workflow for the evaluation of cfDNA and CTCs in NSCLC patients all from one blood sample. Using Vortex technology and EntroGen ctEGFR assay, EGFR mutations were identified at 0.5 ng of DNA (~83 cells), with a sensitivity ranging from 0.1% to 2.0% for a total DNA varying from 25 ng (~4 CTCs among 4000 WBCs) to 1 ng (~4 CTCs among 200 WBCs). The processing of plasma-depleted-blood provided comparable capture recovery as whole blood, confirming the possibility of a multimodality liquid biopsy analysis (cfDNA and CTC DNA) from a single tube of blood. Different anticoagulants were evaluated and compared in terms of respective performance. Blood samples from 24 NSCLC patients and 7 age-matched healthy donors were analyzed with this combined workflow to minimize blood volume needed and sample-to-sample bias, and the EGFR mutation profile detected from CTCs and cfDNA compared to matched tumor tissues. Despite the limited size of the patient cohort, results from this non-invasive EGFR mutation analysis are encouraging and this combined workflow could represent a valuable means for informing therapy selection and for monitoring treatment of patients with NSCLC.